In Touch : the newsletter of the Irish Gay Rights Movement. (Dublin : IGRM vanaf (1981-1982) 3 NGF, 1980)
Fonds Suzan Daniel (FSD)
Periodiciteit : maandelijks
Redactie : PO Box 739, Dublin 8 ; vanaf (1981-1982) 3 : 10 Fownes Street, Dublin 2
Vanaf (1981-1982) 3 : journal of the National Gay Federation
Engels
Periodiek